ANALYSIS OF THE RELATIONSHIP BETWEEN PRODUCT QUALITY PERCEPTION AND CALL CENTER SERVICE ON CUSTOMER RECOMMENDATION INTENTION IN THE TELECOMMUNICATION INDUSTRY: A SYSTEMATIC LITERATURE REVIEW - Norma Handayani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Digital transformation has driven fundamental changes in Indonesia’s telecommunications industry, where perceived product quality and the effectiveness of customer service are key factors in sustaining customer loyalty and advocacy. This study analyzes the relationship between perceptions of product quality and Call Center service on customers’ recommendation intention using a Systematic Literature Review (SLR) approach. The literature search strategy employed combinations of Boolean keywords across Scopus, ScienceDirect, and Google Scholar for the 2020–2025 period, yielding 19 articles that met the inclusion criteria. The analysis shows that perceived product quality and service quality are primary determinants influencing satisfaction, trust, and loyalty, which in turn lead to recommendation intention. The reliability, responsiveness, and assurance dimensions of call center services strengthen customers’ perceptions of the company’s professionalism and empathy, while high perceived product quality increases customers’ willingness to recommend the service to others. The study affirms that the synergy between product excellence (network stability and the reliability of product services) and customer service interactions (Call Center) plays a significant role in shaping a holistic customer experience. Practically, these findings offer strategic implications for telecommunication industry practitioner to enhance the integration of product and service quality to build sustainable customer advocacy in the digital era. Future research is recommended to develop an integrative model that examines the simultaneous influence of product quality and Call Center service quality on customers’ recommendation intention by incorporating satisfaction, trust, and emotional experience as mediating variables within the context of converged digital services.